ADVENTURE TOURISM AN INSUFFICENTLY EXPLOITED OPPORTUNITY IN BIHOR COUNTY, ROMANIA - Anamaria Liana LĂZURAN (GIURĂU) (Analele Universităţii din Oradea: Seria Geografie, 2014)
The routine of everyday life, the stifling society, the desire of novel and unexpected alongside the unlimited access to information got the modern man on the threshold of a new experience: adventure. Within this context in the tourism industry one type of tourism seems to gain more and more followers: adventure tourism. The adventure tourism is a nature-based tourism involving challenging outdoors activities with a great potential of thrill and excitement. Thus, this paper aims to emphasise the potential for adventure tourism in Bihor County by highlighting the areas where activities related to adventure tourism are developed and to propose new itineraries.